The Body and Technology. A Contribution to the Bioethical Debate on Sport - Zagorac, Ivana (Array, 2010)
The differences between the image of top athletes in history and those today could meet at the intersection between cyborg theory and sport studies. The reconceptualisation of athletes could at first be viewed as a shift from the "natural" to the "artificial". Throughout history top athletes have always been considered to be somehow unnatural, and have always been celebrated as heroes who have overcome the boundaries of their natural bodies. Today’ s sports events have been attracting more viewers than ever before, and tough competition has been raising the very standards of competition. High attendance sports are already freak shows ; whether from the comfort of their homes or from the grandstands, it is difficult for sport supporters to imagine themselves sculpting such a super-muscular body with super-fast reflexes. Old-fashioned blood, sweat and tears are still present somewhere, although they are incorporated into the advanced achievements of the modern techno-culture. A number of the issues raised from this perspective have found room for discussion in the relatively new pluri-perspectival approach to the challenges of the biotechnological era – in bioethics. Bioethics offers a platform for a dialogue on the key questions of today’ s world, a dialogue that surpasses disciplinary, expert, historical and cultural positions. However, any such discourse is facing a pluralism of approaches and methodological barriers, and presupposes the existence of adequate theoretical grounds. This paper highlights only some of the problem points that plastically outline the insufficiencies of the existing mono-perspectively guided conceptions in the field of sport. Accordingly, the authoress emphasises only some of the symptoms that point to the disorientedness of everyday life, which is portrayed in sport in a rather peculiar way: the fragility of the ethical positions contained in the concepts of the "spirit of sport" and fair play in facing the developments of science and technology, the objectification of the body, and an increase in the people’ s interest in high-risk activities. The authoress views these traits as signs of the need to transcend the until recently prevalent reductionistic and mono-perspectival approaches, which the distinctive bioethical approach can indeed do.